Das akute Abdomen = Acute abdominal pain - Becker, Peter; Böttcher, Knut A.; Schilling, Dieter (Deutsche medizinische Wochenschrift, 2017)
Acute abdominal pain is a potentially life-threatening condition that requires a concise and quick workup. Patient history, physical examination and laboratory studies help to establish a working diagnosis. If abdominal Ultrasound is not conclusive, contrast-enhanced Computertomography should be performed. Every patient should be treated aggressively for pain control and fluid substitution independent of the diagnostic workflow. In cases of severe disease, initiation of broad spectrum antibiotic therapy should be considered early.
Auf der Frontdoor mit engl. Paralleltitel: Acute abdominal pain
Publikationsdatum: 22. März 2017 (online)
Gesehen am 17.10.2018